IKLIM KOMUNIKASI ORGANISASI DAN SEMANGAT KERJA PARA PERSONIL POLRI DI POLWIL SURAKARTA - Hastasari, Chatia (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2015)
POLRI has hierarchy organization same with other military institution. The occupation placement based on level of promotion, higher position of the POLRI’s promotion increase their occupation and their welfare. However, the higher level of lobby to the leader will determine the occupation, because not all occupation in police can increase the welfare of their personnel. This is the cause of polemic in police institution. The purpose of this research is to know the significant relation between organizational communication condition and working spirit of the POLRI’s personnel in POLWIL Surakarta and to know the significant relation between social economy status and the organizational communication condition and working spirit of the Polri’s personnel in POLWIL Surakarta. The type of this research is explanatory research thet will explain the causal relation between its variable through hypothesis examination. The research used survey method that take sample from population and uesd questioner as the primary data collector. The research take 76 sample use Yamane formula. There are 3 variables where the relation between independent variable (organzational communication condition) and dependent variable (working spirit) will be presented by third variable that will be controled its effect (social economy status), so the writer used Kendall partial correlation coefficient. Based on the whole data analysis result, it can be concluded that among the three variables namely, organzational communication condition (X), working spirit (Y) and social economy status (Z), the result is 0,752. the early value of Txy was 0, 765 and after the effect was controlled by social economy status (Z) becomes 0, 752. so, it decrease about 0, 013. it means that social economy status is not the particular things that effect the communication condition and working spirit owned by the personnel of POLRI in POLWIL Surakarta.